2021
DOI: 10.1029/2020gl091741
|View full text |Cite
|
Sign up to set email alerts
|

Future Sea Level Change Under Coupled Model Intercomparison Project Phase 5 and Phase 6 Scenarios From the Greenland and Antarctic Ice Sheets

Abstract: We compare results from an ice sheet model inter-comparison forced using CMIP6 and CMIP5 climate projections• Projected sea level at 2100 is higher for Greenland under CMIP6 scenarios than CMIP5, but similar for Antarctica under both scenarios• CMIP6 warmer climate results in increased Greenland surface melt while increased snowfall mitigates loss from ocean warming for Antarctica

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 27 publications
2
48
0
Order By: Relevance
“…The future climate simulations carried out in this study for the GrIS over the 3rd millennium confirm and continue the trends that were reported by ISMIP6-Greenland for the 21st century (Goelzer and others, 2020; Greve and others, 2020b; Payne and others, 2021). The response of the ice sheet is mainly governed by a negative SMB due to increased surface melting near the ice margin.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The future climate simulations carried out in this study for the GrIS over the 3rd millennium confirm and continue the trends that were reported by ISMIP6-Greenland for the 21st century (Goelzer and others, 2020; Greve and others, 2020b; Payne and others, 2021). The response of the ice sheet is mainly governed by a negative SMB due to increased surface melting near the ice margin.…”
Section: Discussionsupporting
confidence: 87%
“…The atmospheric forcing consists of a 1960–1989 reference climatology, plus space-time-dependent anomalies for SMB and ST. These were derived from a systematic sampling of CMIP5 GCMs that reflects their spread in future projections (Barthel and others, 2020), while CMIP6 GCMs were added on the basis of availability only (Payne and others, 2021). All GCM forcings were downscaled to the GrIS surface with the regional climate model MAR v3.9.6 (Fettweis and others, 2017; Delhasse and others, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The quadratic extrapolation is supported by Ice Sheet Model Intercomparison 6 (ISMIP6) of the Coupled Model Intercomparison Project Phase 6 (CMIP6) projections of Antarctica's contribution to sea-level rise until the year 2100, which suggest a time evolution well-approximated by a second-order polynomial, across models and model set ups, as well as using various climate forcing (Payne et al, 2021). Note, however, that despite similar temporal characteristics of the projections, the complex interplay of physical processes in response to the climate forcing governs the actual path of each simulation.…”
Section: Extrapolation Of Sea-level Contributionmentioning
confidence: 88%
“…First, mass balance and dynamic acceleration are assumed to prevail unchanged until the end of this century, implying no changes in the external forcing. Next, we neglect possible long-term changes in SMB, which have been shown to have an important impact on the sea-level contribution Payne et al (2021). In addition, we extrapolate present-day mass balance components based on a relatively short time period of 19 years.…”
Section: Extrapolation Of Sea-level Contributionmentioning
confidence: 99%
See 1 more Smart Citation